Faktor-Faktor yang Berhubungan dengan Keluhan Musculoskeletal Disorders pada Pekerja Usaha Mikro Kecil Menengah Kerupuk di Kota Palembang - Audhy Hidianti Salsabila; Maliha Amin; Maksuk, Maksuk; Faiza Yuniati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Musculoskeletal Disorders (MSDs) are common occupational health problems, especially among workers in the informal sector such as micro, small, and medium enterprises producing crackers in Palembang City, whose activities are dominated by manual work with non-ergonomic postures. This study aimed to analyze the factors associated with MSDs complaints among MSME cracker workers in Palembang. This quantitative research used a cross-sectional design. Data were collected in June 2025 through observation and structured questionnaires from 107 workers across 27 MSMEs. Independent variables included individual factors (age, sex, body mass index/BMI, smoking habits) and occupational factors (work posture, years of service, and working duration). Data were analyzed using univariate and bivariate analyses with chi-square tests. The results showed that 70.1% of respondents reported MSDs complaints. Statistical analysis revealed significant associations between BMI (p = 0.027), work posture (p = 0.026), years of service (p = 0.000), and working duration (p = 0.000) with MSDs complaints. The most dominant factor was years of service (OR = 8.54; 95% CI: 3.33–21.89). In conclusion, MSDs complaints among MSME cracker workers in Palembang were influenced by both individual and occupational factors, with years of service being the strongest predictor. Preventive efforts such as ergonomic interventions, working hours regulation, and occupational health promotion are essential to reduce the risk of MSDs.